2016
DOI: 10.1371/journal.pone.0169166
|View full text |Cite
|
Sign up to set email alerts
|

People Like Logical Truth: Testing the Intuitive Detection of Logical Value in Basic Propositions

Abstract: Recent studies on logical reasoning have suggested that people are intuitively aware of the logical validity of syllogisms or that they intuitively detect conflict between heuristic responses and logical norms via slight changes in their feelings. According to logical intuition studies, logically valid or heuristic logic no-conflict reasoning is fluently processed and induces positive feelings without conscious awareness. One criticism states that such effects of logicality disappear when confounding factors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…This way of operating generates two kinds of intuitive responses: heuristic responses, which are based on stereotypical associations, and logical responses, which are based on automatically activated elementary knowledge of logico-mathematical principles. This brings up the question of hybrid models (Bago & De Neys, 2017; Banks, 2017; De Neys, 2012; Epstein, 1994; Handley & Trippas, 2015; Johnson et al, 2016; Nakamura & Kawaguchi, 2016; Pennycook et al, 2014, 2015; Sloman, 1996; Smith & DeCoster, 2000; Thompson & Johnson, 2014; Trippas et al, 2016, 2017; Trippas & Handley, 2017). Bago et al (2018) developed a hybrid dual-process model in which the faster System 1 thinking cues both heuristic, belief-based responses (stereotypes) and elementary logico-mathematical principles (base rates).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This way of operating generates two kinds of intuitive responses: heuristic responses, which are based on stereotypical associations, and logical responses, which are based on automatically activated elementary knowledge of logico-mathematical principles. This brings up the question of hybrid models (Bago & De Neys, 2017; Banks, 2017; De Neys, 2012; Epstein, 1994; Handley & Trippas, 2015; Johnson et al, 2016; Nakamura & Kawaguchi, 2016; Pennycook et al, 2014, 2015; Sloman, 1996; Smith & DeCoster, 2000; Thompson & Johnson, 2014; Trippas et al, 2016, 2017; Trippas & Handley, 2017). Bago et al (2018) developed a hybrid dual-process model in which the faster System 1 thinking cues both heuristic, belief-based responses (stereotypes) and elementary logico-mathematical principles (base rates).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It now appears that the empirical “defective” table for the conditional should be called the “2 × 2 de Finetti table” (and similarly for the “defective” biconditional) to avoid the negative term “defective” (Milne, 2012 ; Baratgin et al, 2013 , 2014 ; Nakamura and Kawaguchi, 2016 ). Notice (Table 1 ) that in columns 1 and 3 the empirical “defective” table bears a symbol ”I“ (for irrelevant ), whereas in column 1′ and 3′ the 2 × 2 de Finetti tables bear the symbol “∅” (for void ).…”
Section: The De Finettian Approachmentioning
confidence: 99%
“…The goal of Experiment 2 was to replicate the findings of Experiment 1 and to investigate the relationship between our pseudo-logical conflict effects and cognitive ability. Contrary to expectations, it has been observed that logical intuitions are most likely to be observed amongst high-rather than low-ability reasoners (Erceg et al, 2019;Frey et al, 2017;Hayes et al, 2020;Raoelison et al, 2020;Šrol & De Neys, 2020;Thompson et al, 2018;Thompson & Johnson, 2014; but see, Ghasemi et al, 2021;Howarth et al, 2018;Markovits et al, 2020;Nakamura & Kawaguchi, 2016). The explanation given for this relationship is that high ability reasoners have learned (at least simple) logical inferences to the point of automaticity (Stanovich, 2018;Thompson et al, 2018), so that they interfere with the ability to make belief-based judgement.…”
Section: Discussionmentioning
confidence: 63%
“…In Experiment 2, we used the same materials and design, but presented participants with two measures of cognitive capacity. Whilst several studies have showed that reasoners with higher cognitive capacities have increased intuitive sensitivity to logical validity (Erceg et al, 2019;Frey et al, 2017;Raoelison et al, 2020;Šrol & De Neys, 2020;Thompson et al, 2018;Thompson & Johnson, 2014), others have failed to find such a relationship between logical intuition capacity and cognitive ability (Ghasemi et al, 2021;Markovits et al, 2020;Morsanyi & Handley, 2012;Nakamura & Kawaguchi, 2016). The goal of this experiment was to test whether higher ability participants are similarly sensitive to both logic and pseudo-logic structures.…”
Section: The Present Studymentioning
confidence: 98%
See 1 more Smart Citation